Haemato-Epidemiological Study of Peste des Petits Ruminants in Goats - Patel, Mayank A; Mehta, Sudhir A; Patel, Manish D; Parmar, Saurabh M; Bhojani, Rajesh J; Bhoya, Shruti D (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study, conducted from January to September 2024 at the Veterinary Clinical Complex, Kamdhenu University, Navsari, investigated peste des petits ruminants (PPR) in goats, with a 6.38% (29/454) overall incidence, and 40.27% (29/72) hospital-based incidence among suspected cases. Twenty-nine goats out of 454 were confirmed positive using rapid antigen diagnostic test or c-ELISA and s-ELISA. Non descript breeds exhibited the highest incidence (58.62%), followed by Surti (20.68%), Sojat (10.34%), Phantom (6.89%), and Sirohi (3.44%) breeds. Male goats (75.86%) and those aged 1-2 years (55.17%) were predominantly affected. Seasonal trends showed a peak incidence during the monsoon (41.38% in June), with significant influence of age, breed, and sex on disease occurrence. Haematological evaluation revealed macrocytic hypochromic anaemia with elevated mean corpuscular volume and reduced mean corpuscular haemoglobin concentration. Other notable findings included thrombocytopenia, leukopenia, lymphopenia and increase in neutrophil and eosinophil counts, alongside moderate reductions in haemoglobin, total erythrocyte count and packed cell volume in 29 PPR affected goats as compared to 6 healthy control goats.